Alternating atomic-dipole layers and switching dynamics in Al 1-x Sc x N ferroelectrics - Yonghui Zheng; Ruirong Bai; Tianjiao Xin; Xuanyu Zhao; Yan Cheng; Yu-Ning Wu; Yingfen Wei; Binghui Ge; He Tian; Shiyou Chen; Qi Liu; Chungang Duan; et al. (Science, 2026)
Wurtzite Al 1-x Sc x N ferroelectrics exhibit exceptional polarization and thermal stability, making them highly promising for a wide range of electronic applications. However, a more profound understanding is required regarding the atomic-scale mechanism through which cation substitution lowers the switching energy barrier and thus reduces the coercive field. We used spherical aberration–corrected transmission electron microscopy to reveal a periodic modulation of cation-anion spacing along the polarization direction, forming alternating atomic dipole layers. This modulation arises from energetically favorable chemical ordering of aluminum and scandium atoms between adjacent layers, with layer-resolved asymmetry in atomic arrangement. In situ imaging directly captures atomic-scale, noncollective, stepwise polarization switching, revealing intermediate states and local spacing fluctuations. Compositional inhomogeneity in these dipole layers creates multiple transient states that reduce the switching energy barrier. Our findings connect atomic-scale dipole structures to polarization switching kinetics, enabling the rational design of wurtzite ferroelectrics.